Yeast silent mating type loci form heterochromatic clusters through silencer protein-dependent long-range interactions. - Adriana Miele; Kerstin Bystricky; Job Dekker (PLoS Genetics)
The organization of eukaryotic genomes is characterized by the presence of distinct euchromatic and heterochromatic sub-nuclear compartments. In Saccharomyces cerevisiae heterochromatic loci, including telomeres and silent mating type loci, form clusters at the nuclear periphery. We have employed live cell 3-D imaging and chromosome conformation capture (3C) to determine the contribution of nuclear positioning and heterochromatic factors in mediating associations of the silent mating type loci. We identify specific long-range interactions between HML and HMR that are dependent upon silencing proteins Sir2p, Sir3p, and Sir4p as well as Sir1p and Esc2p, two proteins involved in establishment of silencing. Although clustering of these loci frequently occurs near the nuclear periphery, colocalization can occur equally at more internal positions and is not affected in strains deleted for membrane anchoring proteins yKu70p and Esc1p. In addition, appropriate nucleosome assembly plays a role, as deletion of ASF1 or combined disruption of the CAF-1 and HIR complexes abolishes the HML-HMR interaction. Further, silencer proteins are required for clustering, but complete loss of clustering in asf1 and esc2 mutants had only minor effects on silencing. Our results indicate that formation of heterochromatic clusters depends on correctly assembled heterochromatin at the silent loci and, in addition, identify an Asf1p-, Esc2p-, and Sir1p-dependent step in heterochromatin formation that is not essential for gene silencing but is required for long-range interactions.